Translation and validation of the Malay version of Shiffman-Jarvik withdrawal scale and cessation self-efficacy questionnaire: a review of psychometric properties - Teo, E.W.; Lee, Y.Y.; Khoo, S.; Morris, T. (BioMed Central, 2015)
BACKGROUND: Smoking tobacco is a major concern in Malaysia, with 23.1% of Malaysian adults smoking tobacco in 2012. Withdrawal symptoms and self-efficacy to quit smoking have been shown to have significant effects on the outcomes of smoking cessation. The Shiffman-Jarvik Withdrawal Scale (Psychopharmacology, 50: 35-39, 1976) and the Cessation Self-Efficacy Questionnaire (Cognitive Ther Res 5: 175-187, 1981) are two questionnaires that have been widely used in various smoking cessation research. The short SJWS consists of 15 items with five subscales: physical symptoms, psychological symptoms, stimulation/sedation, appetite, and cravings. The CSEQ is a 12-item questionnaire that assesses participant's self-efficacy to avoid smoking in various situations described in each item. The aim of this study was to translate and validate the Malay language version of the SJWS and the CSEQ.